Significance of low-dose radiation distribution in development of radiation pneumonitis after helical-tomotherapy-based hypofractionated radiotherapy for pulmonary metastases - Jo, In-Young (Oxford University Press, 2014)
Hypofractionated radiotherapy (HRT) is now commonly used for pulmonary malignancies, since a tumoricidal dose can be accurately delivered to the target without a consequential dose to adjacent normal tissues. However, radiation pneumonitis (RP) is still a major problem after HRT. To determine the significant parameters associated with developing RP, we retrospectively investigated data from patients with lung metastases treated with HRT using helical tomotherapy. A total of 45 patients were included in the study and the median age was 53 years old. The median prescriptive doses were 50 Gy to the internal target volume and 40 Gy to the planning target volume in 10 fractions over 2 weeks. RP was diagnosed by chest X-ray or computed tomography after HRT, and its severity was determined by CTCAE version 4.0. The incidence of symptomatic RP was 26.6%. Univariate analysis indicated that mean lung doses, V5, V10, V15, V20 and V25 were associated with the development of symptomatic RP (P < 0.05). However, multivariate analysis indicated that only V5 was associated with the development of symptomatic RP (P = 0.019). From the ROC curve, V5 was the most powerful predictor of symptomatic RP, and its AUC (area under curve) was 0.780 (P = 0.004). In addition, the threshold value of V5 for the development of symptomatic RP was 65%. A large distribution of low-dose radiation resulted in a higher risk of lung toxicity. So, to prevent symptomatic RP, it is recommended that the V5 be limited to <65%, in addition to considering conventional dosimetric factors. However, further clinical study must be undertaken in order to confirm this result.